El discurso de Manuela León y su incidencia en la parroquia de cacha provincia de chimborazo periodo 1869-1872 - Mora Solorzano, Natalia Lisset (2016)
This research was conducted to analyze the discourse of Manuela León and its impact on the parish of Cacha, Chimborazo Province, in the period of 1869-1872. The following thesis project consists of four chapters; The first Chapter describes the problem statement, the general and specific objectives, as well as the importance of the issue, so the basic guidelines and the objective of the thesis are constituted and justified. The theoretical foundation is developed in the second Chapter, which is the scientific support, conceptual and doctrinal of the topics developed such as communication and its process, types, styles, theories, social imaginary, discourse and analysis; and finally a review of Cacha parish. The third chapter, the applied methodological process explains; how the information collected in the field research was obtained, and based on this information, the parameters to be considered in the preparation of the proposal were analyzed. In the fourth chapter, after fulfilling the methodical research process, the conclusions and recommendations aimed at analyzing the discourse of Manuela León and its impact on the parish of Cacha Chimborazo Province, 1869-1872 periods are shown.